Phenolic compounds from the twigs and leaves of Tara (Caesalpinia spinosa). Issue 4 (2nd April 2016) - He, Dong-Yang; Li, Yuan-Ping; Tang, Hong-Bo; Luo, Lei; Ma, Rui-Jing; Wang, Ji-Hua; Wang, Li-Qin
Abstract : Two new homoisoflavans, 4′-hydroxy-7-methoxy-3-benzyl-2 H -chromene (1 ) and 3, 4- cis -di- O -3- hydroxy-7-methoxy-3-(4-hydroxybenzyl)-4-ethoxychroman (2 ), one new coumarin, 7-methoxy-3-(4-hydroxybenzyl)coumarin (4 ), together with seven known phenolic compounds, bonducellin (3 ), anemarcoumarin A (5 ), (+)-syringaresinol (6 ), curuilignan D (7 ), scopoletin (8 ), and p -hydroxybenzaldehyde (9 ), were isolated from Tara ( Caesalpinia spinosa Kuntze). The structures of the new compounds were characterized from their 1D and 2D NMR spectral data. All the compounds were isolated from this plant for the first time.